Awesome q2a theme
0 votes
14 views
R1=11(0+1)*

R2=(0+1)* 11

R2=11(0+1)* 11 + 111 + 11

Which is true?

A. L(R1)=L(R2)=L(R3)

B. L(R1) ∪ L(R2)=L(R3)

C. L(R1) ⊆ L(R3)

D. L(R1) ∩ L(R2)=L(R3)

Please answer with proper explanation.
in Theory of Computation by (-5 points)
edited by | 14 views

1 Answer

+1 vote
Best answer

$R1=11(0+1)^*$

$R2=(0+1)^*11$

$R3=11(0+1)^*11+111+11$

$L(R1)=$ set of all the strings starting with 11

$L(R2)=$ set of all the strings ending with 11

$L(R3)=$ set of all the strings starting   and ending with 11

(strings are defined over {0,1})

So it is clear that $L(R3)=L(R1)\cap L(R2)$

by (386 points)
selected by
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
Welcome to GATE CSE Doubts, where you can ask questions and receive answers from other members of the community.
Top Users Jul 2020
  1. Shaik Masthan

    39 Points

  2. hiteshpujari

    9 Points

  3. Venkatesh Akhouri

    6 Points

  4. Meghana518

    6 Points

  5. bittujash

    6 Points

  6. Pawan_k

    6 Points

  7. rits78671

    6 Points

  8. srestha

    6 Points

  9. RavGopal

    4 Points

  10. Sumaiyas

    4 Points

7,543 questions
1,783 answers
10,867 comments
90,482 users